Political islam in the contex of resistive identity and programing in the era of globalization: An Analysis Khalilallahe Sardarnia - Khalilallahe Sardarnia (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2013)
Globalization is a phenomenon that can be viewed from two different angles or be regarded as a natural and objective processes. New changes and discoveries is related to the field of economic and information and communications technologies. Or in the opposite direction, it regards as projects- that is called As "globalization rather than be global"for Expansion of dominance and economy needs of neoliberal capitalist in west.In recent decades, Islamist parties deal with all internal and external constraints to the process of globalization and its projects . In this article, the author seeks to address two important objectives: The rise of political Islam in the base ofresistance to the dominated system and globalization are verified and updated .Through this way, Defensive attitude in Islamic world and its falsehood is revealed and determined. Islam is not violent. So, Strategies for the formation of the movement is offered in the Middle East and North Africa to promote the identity of Islamic world from the resistive level to Democratic government and to reject dominated system in trans-region